Effect Of Age To Overload The Road: (National Road Case Study Tasi Tolu Tibar Timor-Leste) - Francisco Xavier Ajano Ribeiro Dacruz; Sri Wiwoho Mudjanarko (Journal of World Conference (JWC), 2020)
quality of the transportation system in an area is determined by the level of road service that is passed by each vehicle, both light vehicles and heavy vehicles that exceed the overload of the specified class of roads, all of which result in damage to the road faster than the planned age at the beginning of the plan. In this paper, we will see the extent of vehicle overload with the age of road pavement using the Bina Marga 2002 method. The equivalent number is calculated and N (ESAL) is calculated under normal load conditions and overload. So that it can be concluded how the influence of vehicle overload on the age of road pavement. In this final project, it can be seen, for example, by overloading 10% for medium trucks 16 (tons), trailers 34 (tons) and trailers 54 (tons) affecting the percentages of age to 86.455%, 92,515% and 97,858%. For the combination of the three vehicles with an overload of 8%, it affects the percent of planned life to be 92,242% from 100%. So that it can be concluded that the overload of vehicles on road pavement is very influential on the reduction in the age of road pavement so that it can be expected that road users need to comply with existing traffic regulations.